Side effects of long-term antiepileptic drugs on renal tubules of Indonesian children - Partini Pudjiastuti Trihono; Deasy Grafianti; Irawan Mangunatmadja; Mulya Rahma Karyanti (Paediatrica Indonesiana, 2018)
Background Long-term treatment with antiepileptic drugs such as valproic acid (VPA) and carbamazepine (CBZ) may disrupt renal tubular function. Urinary N-acetyl-beta-D-glucosaminidase (NAG) may reflect tubular function and may be useful in detecting early-stage tubular injury. To date, no study has investigated the toxic effect of VPA and CBZ on renal tubules using urinary NAG in Indonesian children. Objectives To determine the toxicity of long-term VPA and/or CBZ treatment on renal tubules in children with epilepsy by measuring urinary NAG index (iNAG). Methods This cross-sectional study was conducted from January to March 2015 at Cipto Mangunkusumo Hospital and Anakku Clinic Pondok Pinang, Jakarta. We included children aged 3 to 16 years with epilepsy on VPA (n=36), CBZ (n=14), or VPA-CBZ combination (n=14) therapy. We measured urinary levels of creatinine and NAG. The urinary NAG reference value was obtained from age-matched healthy controls (n=30). To eliminate diurnal variations in NAG, iNAG was calculated by dividing urinary NAG by urinary creatinine. A urinary iNAG of more than two standard deviations above the mean for healthy children was considered elevated. Results Mean urinary iNAG values for the control, VPA, CBZ, and combination groups were 3.01, 5.9, 4.07, and 6.9 U/g, respectively. All treated groups had higher mean urinary iNAG values compared to the control group. Urinary iNAG was increased in 11/36 children on VPA, 2/14 children on CBZ, and 9/14 children on combination therapy. Conclusion Long-term VPA use may impair renal tubular function, as shown by the increased urinary iNAG. Combination therapy increases damage in the renal tubules.